Integration of scientific experimental data through ontology approach: a review - Azram, Nur Adila; Atan, Rodziah (Asian Research Publication Network, 2016)
Data integration in scientific experiments is important to the scientists in many research domains. This is because many experimental data involved multidiscipline areas and run in different machines or instruments which results in data stored in different ends and human intervention is required in forming a chain of data analysis. Ontology is one of the approaches that have been used in data integration in many domain areas. This paper described and reviewed ontology in data integration effort. Furthermore, the state of research for ontology-based integration of scientific experiment data also covered in this paper.